A Small Glomus Tympanicum Tumor Resected by Minimally Invasive Transcanal Endoscopic Approach - Masafumi Ohki; Shigeru Kikuchi (Case Reports in Otolaryngology)
We present a case of the transcanal endoscopic resection of a glomus tympanicum tumor. A 51-year-old woman presented with pulsatile tinnitus of the right ear persisting for 6 months. A reddish mass was observed through her tympanic membrane. A computed tomography scan revealed a small mass in the mesotympanum. She was diagnosed with a right-sided glomus tympanicum tumor. The glomus tympanicum tumor was classified as type 1 using the Glasscock–Jackson classification, class A using the Fisch classification, and class A1 using the modified Fisch and Mattox classification. The tumor was transcanally and completely resected by endoscopy without any complication. Before and after the surgery, pure-tone audiometry showed a normal hearing level. Preoperative right-sided pulsatile tinnitus resolved after the surgery. Transcanal endoscopic ear surgery is a favorable surgical method for small localized glomus tympanicum tumors.